Respuesta :

Step-by-step explanation:

1).

[tex] \frac{x}{8} = \frac{9}{24} [/tex]

Cross multiply

We have

24x = 72

Divide both sides by 24

That's

[tex] \frac{24x}{24} = \frac{72}{24} [/tex]

We have the answer as

x = 3

2).

3x² + 2x - 10

when x = - 1

Substitute the value of x into the expression

That's

3(-1)² + 2(-1) - 10

= 3 - 2 - 10

We have the answer as

- 9

When x = 0

That's

3(0) + 2(0) - 10

= - 10

When x = 1

That's

3(1)² + 2(1) - 10

= 3 + 2 - 10

= 5 - 10

= - 5

3).

[tex] \sqrt{( - 9)} [/tex]

First of all apply the radical rule

That's

[tex] \sqrt{ - a} = \sqrt{ - 1} \times \sqrt{a} [/tex]

So we have

[tex] \sqrt{ - 9} = \sqrt{ - 1} \times \sqrt{9} [/tex]

Using the imaginary rule

That's

[tex] \sqrt{ - 1} = i[/tex]

We have

[tex] \sqrt{9} \times i[/tex]

We have the final answer as

3i

4).

[tex] \frac{1}{x} [/tex]

when x = 0

We have

[tex] \frac{1}{0} = 0[/tex]

when x = 1

[tex] \frac{1}{1} = 1[/tex]

when x = 2

We have

[tex] \frac{1}{2} [/tex]

Hope this helps you

ACCESS MORE